Microsurgery vs. Gamma Knife Radiosurgery for the Treatment of Brainstem Cavernous Malformations: A Systematic Review and Meta-Analysis - Gao, Xiangyu; Yue, Kangyi; Sun, Jidong; Cao, Yuan; Zhao, Boyan; Zhang, Haofuzi; Dai, Shuhui; Zhang, Lei; Luo, Peng; Jiang, Xiaofan (Frontiers in Neurology, 2021)
Background: Brainstem cavernous malformations (BSCMs) are a subset of cerebral cavernous malformations with precarious locations and potentially devastating clinical courses. The effects and outcomes of treating BSCMs by microsurgery or gamma knife radiosurgery (GKRS) vary across studies. Methods: We searched the Medline, Web of Science, The Cochrane Library, PubMed, and China Biology Medicine disc databases for original articles published in peer-reviewed journals of cohort studies reporting on 20 or more patients of any age with BSCMs with at least 80% completeness of follow-up. Results: We included 43 cohorts involving 2492 patients. Both microsurgery (RR=0.04, 95% CI 0.01-0.16, P<0.01) and GKRS (RR=0.11, 95% CI 0.08-0.16, P<0.01) demonstrated great efficacy in reducing the rehemorrhage rate after treatment for BSCMs. The incidence rates of composite outcomes were 19.8 (95% CI 16.8-22.8) and 15.7 (95% CI 11.7-19.6) after neurosurgery and radiosurgery, respectively. In addition, we found statistically significant differences in the median numbers of patients between neurosurgical and radiosurgical cohorts in terms of symptomatic intracranial hemorrhage (ICH; neurosurgical cohorts: median 0, range 0-33; radiosurgical cohorts: median 4, range 1-14; P<0.05) and persistent focal neurological deficit (FND; neurosurgical cohorts: median 5, range 0-140; radiosurgical cohorts: median 1, range 0-3; P<0.05). Conclusions: The reported effects of treating BSCMs by microsurgery or GKRS are favorable for reducing recurrent hemorrhage from BSCMs. Patients in the neurosurgery cohort had a lower incidence of symptomatic ICH, while patients in the radiosurgical cohort had a lower incidence of persistent FND.